2021
DOI: 10.5639/gabij.2021.1001.002
|View full text |Cite
|
Sign up to set email alerts
|

Biosimilars – status in July 2020 in 16 countries

Abstract: The World Health Organization has provided specific guidance for biosimilar products to assist regulators, manufacturers and other professionals involved in the development and evaluation of these products. The development and approval of biosimilars are important for health care, as they allow the marketing of safe, efficacious and affordable biological products. Since the first biosimilars were approved in the EU in 2006, a series of biosimilars have been approved in many countries/geographical regions. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…As Table S1 of the ESM shows, this mainly concerns 'older' generation biologics, such as locally produced epoetin alfa, filgrastim and insulins, which have been approved before 2006 in the respective country of manufacturing. This is also supported by the findings of Kang et al, who showed that the majority of follow-on biologics that cannot be considered biosimilars (termed non-innovator biologics by the WHO) are found in the product classes of insulins, filgrastim, interferons and epoetin alfa [8,13]. This may not be surprising as, historically, these older generation biologics comprise smaller and less complex products, which are easier to replicate and may therefore be more likely to trigger generic competition by local manufacturers.…”
Section: Majority Of Follow-on Biologics Are Not Available In Major B...supporting
confidence: 59%
See 2 more Smart Citations
“…As Table S1 of the ESM shows, this mainly concerns 'older' generation biologics, such as locally produced epoetin alfa, filgrastim and insulins, which have been approved before 2006 in the respective country of manufacturing. This is also supported by the findings of Kang et al, who showed that the majority of follow-on biologics that cannot be considered biosimilars (termed non-innovator biologics by the WHO) are found in the product classes of insulins, filgrastim, interferons and epoetin alfa [8,13]. This may not be surprising as, historically, these older generation biologics comprise smaller and less complex products, which are easier to replicate and may therefore be more likely to trigger generic competition by local manufacturers.…”
Section: Majority Of Follow-on Biologics Are Not Available In Major B...supporting
confidence: 59%
“…In contrast to previous studies looking into general marketing authorisation applications of biosimilars, this study adds granularity by identifying and distinguishing between different follow-on biologics [ 13 ]. In order to do so, we defined the manufacturer of the active substance as the primary unit of analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other important issues relate to the practice of interchangeability and the naming and labelling of biosimilars. Survey details and outcomes have been published [ [6] , [7] , [8] ].…”
Section: Progress and Experience Over The Past Ten Yearsmentioning
confidence: 99%